2016
DOI: 10.1093/ehjci/jew274
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative plaque features from coronary computed tomography angiography to identify regional ischemia by myocardial perfusion imaging

Abstract: Quantitative plaque features obtained from CCTA, LDNCP, and CD, are associated with ischemia by MPI independent of stenosis. LDNCP burden and CD are associated with ischemia in stenosis 30-69% and ≥ 70%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
2
26
0
3
Order By: Relevance
“…Suitable modifications to Imaged coronary anatomy may not be reflective of the true phasic changes of vessel diameter Implementation of automatic algorithms and iterative reconstructions to correct for motion artifacts [102], calcium blooming and stents [103,104], image noises etc. ECG-gated dynamic CTA imaging will capture phasic anatomic changes of the coronaries, however this will introduce more radiation [105] Elastic wall modeling may be implemented using FSI simulations to capture the wall movement [66] Segmentation and 3D model reconstruction Imaging artifacts make it difficult to segment the images and detect the true lumen borders Segmentation of the coronary artery lumen, plaque and wall is a tedious and time-consuming process Implementation of clinically used semi-automatic algorithms have improved quantitative luminal assessment [63,106] Implementation of fully automized segmentation tools utilizing deep learning algorithm may increase the accuracy and decease labor intensive segmentation process [95] Fluid dynamic simulation…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Suitable modifications to Imaged coronary anatomy may not be reflective of the true phasic changes of vessel diameter Implementation of automatic algorithms and iterative reconstructions to correct for motion artifacts [102], calcium blooming and stents [103,104], image noises etc. ECG-gated dynamic CTA imaging will capture phasic anatomic changes of the coronaries, however this will introduce more radiation [105] Elastic wall modeling may be implemented using FSI simulations to capture the wall movement [66] Segmentation and 3D model reconstruction Imaging artifacts make it difficult to segment the images and detect the true lumen borders Segmentation of the coronary artery lumen, plaque and wall is a tedious and time-consuming process Implementation of clinically used semi-automatic algorithms have improved quantitative luminal assessment [63,106] Implementation of fully automized segmentation tools utilizing deep learning algorithm may increase the accuracy and decease labor intensive segmentation process [95] Fluid dynamic simulation…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…43,44 Another potential utility of coronary CTA is to predict ischemia by assessing plaque stenosis, morphology and/or volume. [52][53][54][55][56] have revealed that increased prevalence of high-risk plaque features was associated with ischemia, especially when positive remodeling and low attenuation plaque were present. 52 Diaz-Zamudio et al has investigated if plaque characteristics assessed by quantitative CT software can predict ischemia and found that total, non-calcified and low attenuation plaque burden were associated with ischemia.…”
Section: Intra-/inter-reader Variability Of Plaque Imaging By Coronarmentioning
confidence: 99%
“…52 Diaz-Zamudio et al has investigated if plaque characteristics assessed by quantitative CT software can predict ischemia and found that total, non-calcified and low attenuation plaque burden were associated with ischemia. 55 Conversely, there are only few reports on the prediction of ischemia by IVUS or OCT. [57][58][59] Coronary CTA may be a potential approach because the entire coronary vessel can be evaluated for atherosclerosis, allowing for detailed information to identify ischemia (as compared to only segmental plaque information by IVUS or OCT). However, there have been no such studies on head to head comparison of these invasive and noninvasive imaging modalities for predicting ischemia.…”
Section: Intra-/inter-reader Variability Of Plaque Imaging By Coronarmentioning
confidence: 99%
“…In einer erst kürzlich publizierten Studie von Diaz-Zamudio et al [20] wurden aus der CCTA mittels einer semi-automatischen "Autoplaque Software" [18] die Koronarplaque-Eigenschaften 3-dimensional und quantitativ nach unterschiedlichen Kriterien beurteilt und mit der Ischämie aus der MPS in Beziehung gesetzt. Hier zeigte sich u.a., dass einzelne quantitative Plaque-Eigenschaften, unabhängig von deren Stenosegrad, mit einer Ischämie assoziiert sind.…”
Section: Stress Restunclassified